A Study of Components of Innovator Competency of School Administrators - Hodluecha, Naluedon; Phengsawat, Waro; Tameruk, Tharathep (Journal of Graduate MCU KhonKaen Campus, 2026)
This research aimed to investigate the components of innovative competency among educational administrators. The research was carried out in two distinct phases. The first phase involved synthesizing innovative competency components through a systematic review of 10 relevant documents and research studies. A document synthesis form was used as the research instrument. Descriptive statistics, including frequency and percentage, were used for data analysis. In the second phase, five experts evaluated the appropriateness of the identified components. A five-point Likert scale questionnaire was employed as the research instrument, and the data were analyzed using mean scores and standard deviation. The findings revealed that the innovative competency components for educational administrators consisted of four key dimensions: (1) Creative Skills, (2) Content knowledge and practical skills, (3) Networking, and (4) Leadership. Overall, all components were rated at the highest level of appropriateness.